2020
DOI: 10.1093/noajnl/vdaa103
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characterization of a multi-institutional cohort of pediatric spinal cord low-grade gliomas

Abstract: Background The MAPK/ERK pathway is involved in cell growth and proliferation, and mutations in BRAF have made it an oncogene of interest in pediatric cancer. Previous studies found that BRAF mutations as well as KIAA1549-BRAF fusions are common in intracranial low-grade gliomas (LGGs). Fewer studies have tested for the presence of these genetic changes in spinal LGGs. The aim of this study was to better understand the prevalence of BRAF and other genetic aberrations in spinal LGG. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
(49 reference statements)
1
12
0
Order By: Relevance
“…It has been largely investigated and demonstrated that KIAA1549-BRAF-fused cerebellar pLGGs have a better prognosis compared to the ones not carrying the fusion; the same evidence has been described for the spinal low-grade gliomas [ 13 , 15 ]. On the other hand, the presence of BRAF fusion in the tumor suggests the potential use of target therapy, such as MEK inhibitors [ 16 ], while the use of BRAF inhibitors are indicated and useful when the BRAFV600 mutation is present [ 17 ].…”
Section: Gliomas and Mixed Neuronal–glial Tumorsmentioning
confidence: 89%
See 3 more Smart Citations
“…It has been largely investigated and demonstrated that KIAA1549-BRAF-fused cerebellar pLGGs have a better prognosis compared to the ones not carrying the fusion; the same evidence has been described for the spinal low-grade gliomas [ 13 , 15 ]. On the other hand, the presence of BRAF fusion in the tumor suggests the potential use of target therapy, such as MEK inhibitors [ 16 ], while the use of BRAF inhibitors are indicated and useful when the BRAFV600 mutation is present [ 17 ].…”
Section: Gliomas and Mixed Neuronal–glial Tumorsmentioning
confidence: 89%
“…Mutations in genes encoding histone H3.1 (HIST1H3B) and H3.3 (H3F3A) have been considered as a hallmark of diffuse midline gliomas. Instead, histonic mutations are also rarely found in pediatric low-grade gliomas [ 19 ]; this concept is important in highlighting the pathological heterogeneity in gliomas and the overlapped genetic landscape between high- and low-grade gliomas [ 13 , 20 ].…”
Section: Gliomas and Mixed Neuronal–glial Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have shown that the main recurrent molecular alterations are KIAA1549-BRAF fusions and H3F3A p . K27M (H3K27M) mutations ( 9 , 10 ), while others did not identify recurrent molecular alterations at all ( 11 ). Interestingly, the most frequent molecular alterations found in brain astrocytomas, such as IDH mutations, are generally not observed in IMAs or were not classic IDH1 p. R132H and IDH2 p. R172H mutations ( 9 , 11–17 ).…”
Section: Introductionmentioning
confidence: 99%